Absent ice patches and the continued reliability of caribou as a resource to prehistoric hunters throughout the Holocene - Koszalinski, Holly Lynn (My University, 2011)
Ice patches have recently exploded as a new field of research in archaeology and as a vital source to understanding prehistory. The uniqueness of ice patch archaeology lies within the preservation of organic materials offering exceptional information about cultural behavior. Ice patches were traditionally used as hunting locations throughout prehistoric and protohistoric times. With rapidly changing climate conditions, ice patches are melting quickly and in some cases surface ice has completely melted away leaving behind the accumulation of caribou dung. In the 2010 field season, the Basalt Lake ice patches within the Denali Highway region of central Alaska were surveyed and it was observed that caribou still frequented the area even in the absence of surface ice. This paper will examine the significance of continual use of ice patch areas by caribou in the absence of surface ice and what this meant for prehistoric hunters throughout the Holocene during greater climatic shifts.
Keywords: Paleoecology -- Holocene.; Caribou hunting -- Northern Hemisphere -- History.; Prehistoric peoples -- Food -- Northern Hemisphere.; Hunting, Prehistoric -- Northern Hemisphere.